Multi-physics effects on the performance of Dense-array Concentrator Photovoltaic System. (February 2019) - Ju, Xing; Pan, Xinyu; Xu, Chao
Abstract: In this paper, the multi-physics effects on the performance of dense array concentrator photovoltaic (DA-CPV) system are investigated in detail by considering CPV module connections, non-uniform illumination, and temperature distribution. It is observed that the optimized module configuration can significantly reduce the overall cells temperature and then improve the efficiency and stability. We also analyze the effects of temperature uniformity on output performance. When the illumination, configuration and mean temperature are certain, the temperature distribution can affect the output performance of the DA-CPV system. In the case of non-uniform illumination, the maximum power of the module will be achieved with an inverse Gaussian temperature distribution, instead of uniform temperature. Through this comprehensive understanding the temperature effects of the DA-CPV module, a suitable cooling system can be designed to reduce power loss.